Influence of PdO content and pathway of its formation on methane combustion activity - Choudhary, Tushar V.; Banerjee, S.; Choudhary, Vasant R. (Catalysis Communications, 2005)
The methane oxidation reaction is known to induce changes in the surface structure and composition of Pd catalysts; making it extremely arduous to relate the methane oxidation activity to specific catalyst properties by conventional methods (continuous flow reactor studies). To circumvent this, methodical pulse reactor studies have been undertaken to obtain correlations between the initial methane combustion activity and the catalyst properties (Pd-0/PdO content and path of PdO formation). While the initial methane combustion activity (at 160-280 degreesC) continuously increased with increasing PdO concentration (0-100%) in the catalyst, it continuously decreased with increasing Pddegrees content (0-100%). Controlled studies were undertaken to obtain catalysts with identical PdO content by two pathways: (i) by controlled partial oxidization of Pd-0/Al2O3 and (ii) by controlled partial reduction of PdO/Al2O3. Interestingly, for a given PdO content, the catalysts obtained by partial oxidation of Pd-0/Al2O3 showed a significantly superior performance to the catalyst obtained by partial reduction of PdO/Al2O3 for all the temperatures investigated. These studies unambiguously show that along with the relative concentration of PdO, the PdO formation pathway is also critical in deciding the methane combustion activity of the catalyst. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Methane combustion; Oxidation; partially oxidized Pd-0/Al2O3; partially reduced PdO/Al2O3; Pd-0/Al2O3; PdO/Al2O3; pulse reaction of methane

Nano-gold supported on Fe2O3: a highly active catalyst for low temperature oxidative destruction of methane green house gas from exhaust/waste gases - Choudhary, Vasant R.; Patil, V. P.; Jana, Prabhas; Uphade, B. S. (Applied Catalysis A-General, 2008)
A number of nano-gold catalysts were prepared by depositing gold on different metal oxides (viz. Fe2O3, Al2O3, Co3O4, MnO2, CeO2, MgO, Ga2O3 and TiO2), using the homogeneous deposition precipitation (HDP) technique. The catalysts were evaluated for their performance in the combustion of methane (1 mol% in air) at different temperatures (300-600 degrees C) for a GHSV of 51,000 h(-1). The supported nano-gold catalysts have been characterized for their gold loading (by ICP) and gold particle size (by TEM/HRTEM or XRD peak broadening). Among these nano-gold catalysts, the Au/Fe2O3 (Au loading = 6.1% and Au particle size = 8.5 nm) showed excellent performance. For this catalyst, temperature required for half the methane combustion was 387 degrees C, which is lower than that required for Pd(1%)/Al2O3 (400 degrees C) and Pt(1%)/Al2O3 (500 degrees C) under identical conditions. A detailed investigation on the influence of space velocity (GHSV = 10,000-100,000 cm(3) g(-1) h(-1)) at different temperatures (200-600 degrees C) on the oxidative destruction of methane over the Au/Fe2O3 catalyst has also been carried out. The Au/Fe2O3 catalyst prepared by the HDP method showed much higher methane combustion activity than that prepared by the conventional deposition precipitation (DP) method. The XPS analysis showed the presence of Au in the different oxidation states (Au-0, Au1+ and Au3+) in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Au/Fe2O3; Deposition precipitation; Homogeneous deposition precipitation; Methane combustion; Supported nano-gold catalysts